Groundwater governance in South Asia: governing a colossal anarchy - Mukherji, Aditi; Shah, Tushaar (International Water Management Institute, 2003)
Research highlight based on a paper titled ?Groundwater socio-ecology of South Asia: An overview of issues and evidence?